Behavior of buried sliplined corrugated metal pipes subjected to footing loading - Rahmaninezhad, S. Mustapha; Jawad, Saif; Han, Jie; Al-Naddaf, Mahdi; Parsons, Robert L. (Frontiers in Built Environment, 2025)
Buried structures (e.g., culverts and pipes under roadways) installed several decades ago are reaching the end of their service life. Excavation and replacement of these structures will cause disturbances to the transportation network and require significant funding. Trenchless techniques (e.g., sliplining) have been increasingly employed to rehabilitate deteriorated buried structures (e.g., corroded corrugated steel pipes). Sliplining includes inserting a new pipe (liner) into an existing deteriorated pipe and filling the gap between them with grout. The objective of this study was to evaluate the effect of sliplining on the behavior of buried corrugated steel pipes with different degrees of corrosion under loading. In this experimental study, six footing loading tests were conducted on the unlined and sliplined buried steel corrugated pipes with different degrees of corrosion in soil in a reduced-scale test box under a plane-strain condition. A low-viscosity grout was used to fill the space between the steel pipe and the liner. After the footing loading tests were conducted, the sliplined steel pipes were exhumed from the box for examination and assessment. Then, a series of parallel plate loading tests were carried out on the exhumed rehabilitated pipes using a universal testing machine. The results show that the measured earth pressures induced by footing loading above the crown of the unlined pipe with 0% corrosion were higher than those with 50% and 90% cutout to simulate the degree of corrosion. However, the degree of corrosion did not have a significant effect on the earth pressures induced by footing loading above the crown of the sliplined pipes. From the exhumed pipes, sliplining increased the load-carrying capacities as compared with the unlined steel pipes tested in air.